State of the practice on energy-based liquefaction evaluation and research significance - Takaji Kokusho (AIMS Geosciences)
Since the 1964 Niigata and Alaskan earthquakes, which incurred severe liquefaction damage, liquefaction-related design for infrastructures and buildings has been developed exclusively on the principle of force equilibrium. However, the energy concept is increasingly recognized as superior for simplified and robust liquefaction designs because of the uniqueness of energy capacity in soil failures regardless of the differences in earthquake loads. The energy-based liquefaction evaluation method (EBM) has been pursued by many investigators where dissipated energy for liquefaction is focused in place of liquefaction strength defined in the conventional stress-based method (SBM). Furthermore, the EBM enables sound liquefaction-related designs without resorting to sophisticated but highly variable/tricky numerical analyses and contributes as a scale to measure the reliability of those numerical tools. Thus, the EBM, though short of practical use in today's engineering works, should be able to serve as a simplified liquefaction evaluation tool besides the SBM. We reviewed the basic idea as well as the recent developments of the EBM together with the supporting data. We also discussed how to simplify and approximate the energy-based liquefaction behavior to implement robust evaluations in practical problems. The EBM liquefaction evaluation steps were delineated and exemplified by case studies for practicing engineers compared to the SBM.